Ovarian inflammatory mRNA profiles of a dehydroepiandrosterone plus high-fat diet-induced polycystic ovary syndrome mouse model - Ullah, Amin; Wang, Mei-Jiao; Yang, Jun-Pu; Adu-Gyamfi, Enoch Appiah; Czika, Armin; Sah, Sanjay Kumar; Feng, Qian; Wang, Ying-Xiong (Reproductive biomedicine online, 2022)
What is the expression pattern of inflammatory mRNA profiles of a dehydroepiandrosterone (DHEA) plus high-fat diet (HFD)-induced polycystic ovary syndrome (PCOS) mouse model? RNA sequencing was performed to investigate the mRNA expression profiles in the ovarian tissues of a DHEA plus HFD-induced PCOS mouse model. Six samples were divided into two groups (control and PCOS), with three biological replicates in each group. This was followed by hierarchical clustering, gene ontology and Kyoto Encyclopedia of Genes and Genomes pathway analyses. The relative expression levels of nine inflammatory genes were validated via quantitative reverse-transcription polymerase chain reaction. A total of 436 genes were differentially expressed between the control and PCOS mice. Out of these, 137 genes were up-regulated while 299 genes were down-regulated. Gene ontology analysis indicated that differentially expressed mRNA were associated with T cell-mediated cytotoxicity and homocysteine metabolic processes. Pathway analysis further showed that these abnormally expressed mRNA were associated with signalling pathways, such as NF-kB signalling, tyrosine metabolism and phenylalanine metabolism. All these pathways are involved in chronic inflammation and PCOS. The differentially expressed genes are potentially involved in the inflammation that is evident in PCOS, and so could serve as therapeutic options against the disease. Nevertheless, prospective studies are needed to test this hypothesis.